Systematic ozone and solar UV measurements in the Observatorio Atmosférico de la Patagonia Austral, Argentina - Wolfram, Elian Augusto (2013)
The depletion of the polar ozone layer is one of the strongest anthropogenic signals in the Earth system. Subpolar regions in the southern part of South America are affected by this phenomenon, covered sometimes by air masses with less ozone than normal with the corresponding UV enhancements at ground surface. Motivated by these atmospheric events, Argentina and Chile with the financial support of JICA has joined scientific efforts to develop UVO Patagonia project. The Observatorio Atmosférico de la Patagonia Austral is located in South Patagonia (51º 55?S, 69º 14'W), in the subpolar region and it is a convenient monitoring site of the atmosphere in the Southern Hemisphere. In this experimental site a differential absorption lidar instrument for the measurement of ozone vertical distribution is operative. The altitude range of the ozone measurement is 14-45 km, which provides the opportunity to monitor the turbulences due to the passage of stratospheric polar air over Río Gallegos. Systematic stratospheric ozone profile measurement has been carried on in this experimental site since 2005. We identified three major perturbations of the ozone hole over the stratospheric ozone profile in Río Gallegos. Approach of polar vortex during late winter, overpass of ozone hole in middle spring and dilution process during late spring change the shape and content of stratospheric ozone profile and as a consequence the solar UV. Solar surface irradiance and total ozone content were measured with a Brewer spectraphotometer and moderate narrow band radiometer GUV-541 deployed in the Río Gallegos experimental site.